Uso del Lenguaje No Verbal en la Comunicación: Percepción de los Docentes y los Estudiantes Universitarios (Theological Kronos, 2017)
Non-verbal language has been an issue addressed from different sciences as antropology, psycology, sociology and linguistics. At the same time for common persons the communication seems to be in-complete, by example, when someone receive a phone call he or she can not see nor can they read the feelings and faces that comes out from the person on the other side. This research seeks to identify the use of some elements of the nonverbal language in teaching com-munication; its dynamic structure, its behavior and its manifestation on the university’s classroom. The investigation focuses on twenty (20) teachers and students from the University of Alicante. They were from several backgrounds, contexts, degrees and different levels of educational commitments, also they answered to a formulated and semistructured interview. On this paper we show the use of AQUAD –Analysis of Qualitative Data (Huber, 1988) to analyse the data ob-tained. After being processed the information, we found that the use of nonverbal language in teaching communication can be meanign-ful for each communicative process in the classrrom. However, the differences between teachers and students about the real impact and significant relevance of nonverbal language are evidents
Keywords: non-verbal language, classroom, teacher’s communi-cation, university teaching